Optimal design of Remote Terminal Unit (RTU) for power system operation in smart cities - Aamir, Muhammad (My University, 2013)
The concept of smart cities involves specifically modified infrastructure for its physical, economic and social systems which is mandatory to provide improved facilities to citizens at various levels. The major infrastructure is energy which is mainly distributed in the form of Electricity. Therefore power system operation must be optimized by making it intelligent and environmental friendly by including renewable resources and green ICT systems to achieve greater energy efficiency. In the Europe, the EU has taken an initiative by launching a concrete policy framework to make their cities capable of more energy efficient, reduction of relying on fossil fuels achieving reduction Carbon Dioxide emissions, improved impact by adding renewable energy resources to power grid. The implementation of this significant policy framework would also result in climate improvement. The EU is targeting year 2020 to accomplish such implementations. There are several ways to ensure sustainability but the addition of renewable energy resources with existing grid capacity in an intelligent manner can be an effective solution. In such addition, an optimal generation policy may be developed incorporating power flow model, contingency analysis and determination of good locations. Such generation policy can be implemented using a High Scale SCADA System. In general, the SNMP (Simple Network Management Protocol) based RTUs (Remote Terminal Units) are essential part of SCADA system so an optimal design of RTU for Energy Management System (EMS) is of high interest. This talk will describe contingency analysis with its outcome, Model of Optimized EMS and having focus on Optimal RTU Design including Optimization of RF Communication Link for RTU.
Keywords: Instalaciones energéticas; SCADA; RTU; Smart City